Advanced Revit Architecture 2016 training : go beyond the basics with project-based building information modeling for architects - Myers, Brian L. (O'Reilly, 2015)
"In this Advanced Revit Architecture 2016 training course, expert author Brian Myers takes you beyond the basics of Revit Architecture, allowing you to develop a strong understanding of the tools and techniques available in this Autodesk software. This course is designed for users that already have a working knowledge of Autodesk Revit. You will start by learning how to define the family category and parameters, then jump into setting up annotation standards. From there, Brian will show you how to start the project, link Revit files, create phases, and organize the browser. This video tutorial also shows you how to create walls, curtain walls, floors, stairs, ramps, railings, roofs, and ceilings. You will also learn how to insert, replace and edit groups, and create and modify parts and assemblies. More topics that are covered in this course include areas and rooms, scheduling, and detailing. Finally, you will learn about interior and exterior rendering, and how to share your work. Once you have completed this computer based training course, you will have developed a strong understanding of advanced concepts in Revit Architecture 2016. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.